(untitled) (Progressive Agriculture, 2013)
The experiment was conducted to find out the effect of salt and storage temperature on the quality of sausage. For this purpose sausage samples were divided into two portions. One is called fresh sausage and another is preserved sausage at different temperature. Then the fresh samples as well as the preserved samples were divided into four subdivisions, treated with different salt levels and e.g. control group-0% and the others are 1.5%, 3% and 5% of salt concentration. The preserved samples were stored at 4°C and -20°C. Samples preserved at 4°C were stored in the refrigerator for 21 days and were analyzed on 7th, 14th and 21th day and on the other hand samples preserved at -20°C were stored in the freezer for 60 days and were analyzed on 15th, 30th, 45th and 60th day. Dry matter and Ash content of all the samples increased with the advancement of storage time and salt concentration level. Dry matter in fresh sample was less compared to preserved samples. Crude protein (CP) percent of fresh samples were 23.13, 22.63, 22.48 and 22.44 at different salt concentration level. The values of CP, DM, Ash & Fat also varied among the samples significantly (P<0.01). Sausage can be preserved for 60 days in different techniques with different changes in the quality. Highly significant difference was observed in preserved samples than in fresh samples at different salt levels. Fresh sausage treated with 1.5% salt found to be more acceptable in terms of sensory evaluation. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16561 Progress. Agric. 23(1 & 2): 15 24, 2012